1978
DOI: 10.1080/03014223.1978.10428338
|View full text |Cite
|
Sign up to set email alerts
|

The plasma proteins of some albatrosses and petrels as an index of relationship in the Procellariiformes

Abstract: The plasma proteins of 29 species of albatrosses and petrels were electrophoretically separated in acrylamide gels to clarify relationships at the species-group to family-group levels. Little in the resulting data from 472 birds seriously contests the present classification of the Procellariiformes; much of the biochemical evidence supports, confirms, and clarifies the proposals of conventional taxonomic methodology. The biochemical data give fresh insights into the interrelationships of procellariiform taxa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Furthermore, of the 8 intact skulls among the ROM specimens, all showed full ossification (i.e. fusion) of the frontal/prefrontal bones, confirming their ages as after hatch-year (Harper 1978). Two Smithsonian specimens wrecked by Hugo were molting females, but 1 of them had a bursa, indicating that it was greater than 1 yr old but likely of prebreeding age.…”
Section: Wrecked Petrelsmentioning
confidence: 78%
“…Furthermore, of the 8 intact skulls among the ROM specimens, all showed full ossification (i.e. fusion) of the frontal/prefrontal bones, confirming their ages as after hatch-year (Harper 1978). Two Smithsonian specimens wrecked by Hugo were molting females, but 1 of them had a bursa, indicating that it was greater than 1 yr old but likely of prebreeding age.…”
Section: Wrecked Petrelsmentioning
confidence: 78%
“…The seabird order Procellariiformes comprises the albatrosses, Diomedeidae, and the petrels and shearwaters, Procellariidae. Harper (1978) suggested that ‘petrels were evolving 80–90 million years ago in the Southern Hemisphere along the shores of a fragmenting Gondwanaland’, and Olson (1978) noted that ‘there appears to have been virtually no significant morphological evolution in the Procellariiformes since the middle Miocene’. The Diomedeidae contain two main clades each with two genera (Nunn et al ., 1996), as follows.…”
Section: Panbiogeographic Concepts Appearing In Recent Studiesmentioning
confidence: 99%
“…Investigations of the phylogenetic relationships within the orders Procellariiformes and Sphenisciformes have been characterized by a lack of agreement among authors. For example, the only consistent relationships reported among the Procellariiformes are that they form a monophyletic group with three or four families: Diomedeidae (albatrosses), Hydrobatidae (storm petrels), Procellariidae (gadfly and Procellaria petrels, prions, shearwaters, and fulmarines), and Pelecanoididae (diving petrels); however, relations among and within these families have yet to be satisfactorily resolved (Alexander et al 1965;Brown and Fisher 1966;Sibley and Ahlquist 1972;Jacob 1976;Harper 1978;Imber 1985;Meredith unpubl. thesis 1985;Sibley and Ahlquist 1990).…”
mentioning
confidence: 99%